2020
DOI: 10.1002/adem.202000006
|View full text |Cite
|
Sign up to set email alerts
|

Nature‐Inspired Protecto‐Flexible Impact‐Tolerant Materials

Abstract: The search for impact‐tolerant, light‐weight flexible materials has challenged materials scientists and engineers for decades. In this quest, many researchers have focused on studying natural armor as a guide to propose bioinspired materials with enhanced properties. The energy dissipation and flexibility mechanisms activated at different hierarchical structural levels of natural systems are used here as a guide to improve the energy and flexibility of synthetic materials. In particular, fish scales and osteod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…shown that the impressive toughness enhancement originates from the tablet sliding mechanism 10,[34][35][36] , where millions of tablets slide on one another over large volumes under tensile forces or low-velocity impact loads. Due to the energy-dissipation capacities of different structures depending on their specific failure modes, studies have reported that, upon static loads or a specific low-speed impact, the structures with energy-dissipation abilities from low to high are monolithic structures, laminated structures and nacre-like structures, respectively 10,11,26,27,[37][38][39][40][41][42] . We have collected experimental data on energy dissipations versus loading velocity for nacre-like structures, traditional laminated structures and stiff monolithic structures as shown in the map of Fig.…”
mentioning
confidence: 99%
“…shown that the impressive toughness enhancement originates from the tablet sliding mechanism 10,[34][35][36] , where millions of tablets slide on one another over large volumes under tensile forces or low-velocity impact loads. Due to the energy-dissipation capacities of different structures depending on their specific failure modes, studies have reported that, upon static loads or a specific low-speed impact, the structures with energy-dissipation abilities from low to high are monolithic structures, laminated structures and nacre-like structures, respectively 10,11,26,27,[37][38][39][40][41][42] . We have collected experimental data on energy dissipations versus loading velocity for nacre-like structures, traditional laminated structures and stiff monolithic structures as shown in the map of Fig.…”
mentioning
confidence: 99%
“…In this paper, the suture region of the LL in elasmoid fish scales was evaluated for the first time, and its contribution to the structural behavior of elasmoid scales was characterized. Overall, this feature appears to play a key role in the structural behavior of the scales and is an important element of the topological design in achieving biomimetic materials with so‐called protecto‐flexibility, viz., the multifunctionality consisting of flexibility and toughness 29,48 …”
Section: Discussionmentioning
confidence: 99%
“…Overall, this feature appears to play a key role in the structural behavior of the scales and is an important element of the topological design in achieving biomimetic materials with so-called protecto-flexibility, viz., the multifunctionality consisting of flexibility and toughness. 29,48 An ideal material for "wearable" armor applications would possess low bending stiffness and high toughness. Although important, an increase in strength is not necessarily of direct value to function.…”
Section: Discussionmentioning
confidence: 99%
“…The sample design was inspired by fish scale hierarchical structure (from one to six hierarchical levels), with ultra-high molecular weight polyethylene (UHMWPE) being used as the base material. It has been discovered that these materials can absorb a high level of energy, making them useful as high impact resistant materials [90]. Quasi-static and impact loading conditions were applied to panels of biomimetic ceramic building blocks having different interlocking angles where they were placed on an aluminum frame.…”
Section: Fish Experimental Methods Key Discoveriesmentioning
confidence: 99%